A socio-CFD approach to reduce the possibility of airborne bio-contaminant disease infection in indoor spaces - Randa Khalil; Ahmed El-Kordy; Hesham Sobh (Renewable Energy and Sustainable Development)
This paper introduces a novel socio-CFD method called Epidemic Hybrid Retrofitting (EHR) for enhancing natural ventilation in indoor public spaces to reduce the spread of airborne bio-contaminant diseases, such as COVID-19. The method aims to reduce the infection rate of diseases by improving Indoor Air Quality (IAQ) as a quantitative objective and maximizing user satisfaction as a qualitative objective. The EHR method consists of three phases, with another method called Computational Fluid Dynamics Parametric Optimization (CFDPO) to accelerate the CFD simulation process. The proposed methods were tested in a shared office in Cairo, Egypt, using a combination of observation, investigation, questionnaires, CFD analysis, linear regression analysis, mathematical calculations, and hybrid evaluation. The study observed a recurrence of COVID-19 infections in the case study office, which was attributed to insufficient natural ventilation and occupants' lack of adherence to WHO precautionary measures. Four retrofitting scenarios were suggested based on the application of the CFDPO method. An occupant survey and CFD analysis were conducted to evaluate retrofitting scenarios, and then the Cost Reduction factor (CRf) was introduced and considered. Considering quantitative and qualitative objectives has identified the optimal scenario as Single-centered Openable Windows (SOW) by increasing the window-to-wall ratio (WWR) on the outdoor (north-facing) façade to 14.96% while maintaining a balanced indoor opening design. The optimum solution effectively achieved the desired air change rates and occupant satisfaction. The results demonstrated the applicability of the EHR and CFDPO methods to attain the objectives. The proposed methods can be further adjusted to address additional objectives in future practices.   Received: 21 May 2024 Accepted: 04 August 2024 Published: 10 September 2024